2021
DOI: 10.1021/acsphotonics.1c00149
|View full text |Cite
|
Sign up to set email alerts
|

Using Bottom-Up Lithography and Optical Nonlocality to Create Short-Wave Infrared Plasmonic Resonances in Graphene

Abstract: Graphene plasmonic resonators have been broadly studied in the terahertz and mid-infrared ranges because of their electrical tunability and large confinement factors, which can enable the dramatic enhancement of light–matter interactions. In this work, we demonstrate that the characteristic scaling laws of resonant graphene plasmons change for smaller (<40 nm) plasmonic wavelengths and that those changes modify the optical confinement properties of graphene plasmonic resonators, allowing their operational freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
2
4
0
Order By: Relevance
“…In these simulations, the value of E F at V G = 0 V was chosen as a fitting parameter and calculated spectra were compared to the experimental spectra obtained at V G = 0 V to determine that E F = − 0.55 eV with no gate voltage applied. This indicates that the sample is heavily hole-doped, which is consistent with previous studies of graphene grown and transferred using similar procedures 45 . Using this initial value of E F , the Fermi energies at other gate voltages were derived with a simple capacitance model.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In these simulations, the value of E F at V G = 0 V was chosen as a fitting parameter and calculated spectra were compared to the experimental spectra obtained at V G = 0 V to determine that E F = − 0.55 eV with no gate voltage applied. This indicates that the sample is heavily hole-doped, which is consistent with previous studies of graphene grown and transferred using similar procedures 45 . Using this initial value of E F , the Fermi energies at other gate voltages were derived with a simple capacitance model.…”
Section: Resultssupporting
confidence: 91%
“…The deposition consisted of a 2.5 nm chromium adhesion layer and 30 nm of gold. Following these processing steps, the graphene was found to be heavily hole-doped, similar to what has been observed in previous works 36 , 45 , Gate-dependent resistivity measurements showed an increase in resistance for positive gate bias, but no maximum resistance was observed that would indicate charge neutrality. These measurements also exhibited hysteresis, consistent with what has been observed elsewhere, and indicative of surface, interface, and substrate charge traps that can be populated with charge as V G is changed.…”
Section: Methodssupporting
confidence: 86%
“…Active materials that have been recently investigated for tunable filters include correlated transition-metal oxides with phase transitions 19 , germanium-antimony-tellurium (GST) 20 , and gate-tunable graphene 21 , all of which have complex refractive indices that can be tuned via one or more external stimuli, such as thermal biasing, electrical gating, incident light, and strain. 22,23,24 In particular, thin-film VO 2 -the active medium used in this work-has been widely explored for tunable optical devices, especially in the mid-and far-infrared where it features a high refractive-index contrast, and has relatively low loss in one of its phases.…”
Section: Introductionmentioning
confidence: 99%
“…Active materials that have been investigated for tunable filters include correlated transition-metal oxides, germanium–antimony–tellurium (GST), and gate-tunable graphene, all of which have complex refractive indices that can be tuned via one or more external stimuli, such as thermal biasing, electrical gating, incident light, and strain. In particular, thin-film VO 2 has been widely explored for tunable optical devices, especially in the mid- and far-infrared where it features a high refractive-index contrast and relatively low loss in one of its phases . However, the integration of VO 2 into thin-film assemblies is challenging because of the high temperatures required to obtain the correct crystallographic state (typically, >500 °C ) and the dependence of its electrical and optical properties on the substrate and synthesis methods. , …”
Section: Introductionmentioning
confidence: 99%
“…A planar graphene microribbon is originally placed in xz plane, and is then folded along z axis, to form two segments of width l 1 and l , 2 respectively, and with an angle q between them. In practice, high-quality and large-area graphene can be prepared by chemical vapour deposition (CVD) [66,67], and is further patterned into a microribbon array using standard electron beam lithography [68] or optical lithography [69]. To carry out folding, several experimental techniques have been well developed by using, such as an AFM tip [70,71] or a STM tip [72], a tailored substrate [73], self-assembly [74][75][76], self-folding [77], and a thermally responsive method [78], and these techniques are analysed systematically in a recent review article [79], in which atomically precise folding and unfolding of graphene are intensively discussed.…”
Section: Model Designmentioning
confidence: 99%